Alumni networking programme fosters greater bond among UMP graduates - Nurizzatul Alin, Ahmad Bastani (2019)
To commemorate the 17th anniversary of the foundation of Universiti Malaysia Pahang (UMP), the Alumni Industry Networking Hi-Tea programme for the Northern Zone on March 2, 2019, saw a successful gathering of 60 alumnus, who happily reminisced their student days and campus life at the university.